2016
DOI: 10.1027/1618-3169/a000314
|View full text |Cite
|
Sign up to set email alerts
|

Distraction of Mental Arithmetic by Background Speech

Abstract: When solving mental arithmetic problems, one can easily be distracted by someone speaking in the background and this distraction is greater if the speech comprises numbers.We explored the basis of this disruption by asking participants to solve mental addition problems (e.g. "45 + 17 = ?") in three different conditions: background speech comprising numbers in ascending order (e.g. "61, 62, 63, 64, 65"), background speech comprising numbers in descending order (e.g. "65, 64, 63, 62, 61"), and quiet. Performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
7
2
Order By: Relevance
“…Interestingly, Experiment 1 did not reveal a deviation effect in either task (though there is a small trend for a deviation effect with changing-state sequences on serial recall). Hence, in contrast to several previous observations (Banbury & Berry, 1998 ; Hadlington et al, 2006 ; Perham et al, 2013 , 2016 ; Perham & Macpherson, 2012 ), there was no indication of auditory distraction of mental arithmetic performance in the present study. A possible reason for this could be the use of different types of distractors.…”
Section: Methodscontrasting
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Experiment 1 did not reveal a deviation effect in either task (though there is a small trend for a deviation effect with changing-state sequences on serial recall). Hence, in contrast to several previous observations (Banbury & Berry, 1998 ; Hadlington et al, 2006 ; Perham et al, 2013 , 2016 ; Perham & Macpherson, 2012 ), there was no indication of auditory distraction of mental arithmetic performance in the present study. A possible reason for this could be the use of different types of distractors.…”
Section: Methodscontrasting
confidence: 99%
“…A possible reason for this could be the use of different types of distractors. Most previous studies have shown that mental arithmetic performance was impaired by the presence of speech (e.g., spoken numbers or letters) or continuous office noise with speech, compared to silence or office noise without speech (Banbury & Berry, 1998 ; Hadlington et al, 2006 ; Perham et al, 2016 ; Perham & Macpherson, 2012 ), but they did not contrast conditions of changing-state and steady-state speech as in the present study. Therefore, it could be argued that the disruptions of mental arithmetic in the previous studies may have been due to attentional capture rather than due to interference-by-process produced by the changing-state nature of speech.…”
Section: Methodscontrasting
confidence: 59%
See 1 more Smart Citation
“…2 We believe that distraction-conflict theory not only allows us to conceptualize music as a distraction, but also allows us to organize the literature regarding music and task performance. First, Baron's (1986) proposition regarding structural interference is in line with research on the ISE, in which the task performer is holding task-related items in his or her working memory, and the identity of these items becomes confused with irrelevant sound items (e.g., Neath, 2000;Perham, Marsh, Clarkson, Lawrence, & Sörqvist, 2016). Second, distraction-conflict theory includes the proposition that distractions can affect performance not only through attentional conflict, but also through drive.…”
Section: Music Within the Distraction-conflict Frameworkmentioning
confidence: 78%
“…However, spatial exibility increases the risk that people perform mobile trainings while being around with others or during other cognitively demanding activities, leading to distractions and impairs mindfulness meditation practice (Lawrence et al, 2015). From basic research we know that even quiet music can be distracting which increases by adding voices or disturbing noises (Hygge et al, 2003;Perham et al, 2016;Shih et al, 2012). Therefore, each mindfulness meditation session generally starts with the instruction to choose a place without any disturbance.…”
Section: Level Of Spatial Exibilitymentioning
confidence: 99%